Paediatric chemotherapy prescribing: an audit of pharmacist interventions. Issue 6 (9th May 2013) - Briscoe, L
Abstract : Aim: This audit was undertaken to assess compliance with the Trust 'Operational Policy and Guidance on the Use of Cytotoxic Drugs' when chemotherapy was prescribed in order to highlight common errors and problematic protocols so that prescriber training can be more focused. It also aimed to provide a baseline error rate so that the impact of further electronic prescribing and non-medical prescribing can be assessed. Method: A data collection form was designed and used to collect information from every cycle of prescribed chemotherapy (excluding UKALL03 maintenance prescriptions) over a 5 week period. Information was collected on clinical and non-clinical interventions, type/grade of prescriber, cycle of chemotherapy prescribed and whether or not the cycle was electronically prescribed or completed by hand. Each clinical intervention was graded in terms of severity by the checking pharmacist against set criteria. The grading allocated was checked by another independent pharmacist. Results: 36 cycles of chemotherapy were prescribed and checked over the 5 week period by nine different prescribers. Most cycles were prescribed by consultants. 40 pharmacist interventions were made during the period with a mean intervention rate of 1.1 interventions per cycle of chemotherapy prescribed. The majority of clinical interventions (41%) were graded as minor, 33% as significant, 22% causing no harm, 6% as potentially serious and none as potentially lethal. The most common interventions were related to fluid volumes and supportive therapy. A total of eight non-clinical interventions were made with the most common being prescribers failing to identify that patients were part of a clinical trial. This was closely followed by not providing the required documentation such as oral chemotherapy records. The results also showed that transplant chemotherapy required the most pharmacist interventions. Fifteen of the cycles were prescribed using the electronic prescribing system (Chemocare). There were clear differences between the error rates when comparing electronically prescribed and hand written cycles of chemotherapy. Conclusions: This audit clearly shows the importance of the role of the clinical pharmacist in paediatric chemotherapy. The majority of clinical interventions made were scored as minor with only 6% being scored as potentially serious. The most common clinical interventions relate to supportive therapy and incorrect fluid volumes. Electronic prescribing appears to be having a positive outcome in terms of clinical interventions but having the reverse effect on non-clinical interventions supporting a theory that electronic systems may encourage an absent minded approach to prescribing.